PENGARUH TASK-TECHNOLOGY FIT (TTF) DAN INFORMATION SYSTEM SUCCESS MODEL (ISSM) TERHADAP EFISIENSI KINERJA PELAPORAN KEUANGAN DENGAN KEPUASAN PENGGUNA SEBAGAI VARIABEL INTERVENING - Muhammad Imaduddin Ihsan; Erma Suryani (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Accounting Information Systems (AIS) play an important role in reducing the risk of poor decision-making and promoting efficient managerial performance through the provision of reliable, relevant, timely, complete, and understandable data. One AIS widely used is the ICSO accounting software developed by PT XYZ to support accounting needs ranging from general to detailed levels. However, in several organizations, problems are still found in the form of mismatches between the system and task requirements as well as low user satisfaction, raising the question of whether ICSO truly improves financial management efficiency or merely serves as an information tool. This study integrates the Task–Technology Fit (TTF) approach and the Information System Success Model (ISSM) into a single model with several hypotheses testing the effects of task characteristics, technology characteristics, system quality, information quality, and service quality on task–technology fit, user satisfaction, and the efficiency of financial reporting performance. Data were collected through questionnaires distributed to ICSO users and analyzed using SEM–PLS with SmartPLS 4. The results show that Task Characteristics and Technology Characteristics have a significant effect on TTF; TTF and Information Quality have a significant effect on User Satisfaction; while System Quality and Service Quality are not significant. User Satisfaction has a strong effect on Financial Reporting Performance Efficiency and mediates the effects of TTF and Information Quality on efficiency. These findings indicate that ICSO truly provides added value when its technological functions are aligned with task requirements, produce high-quality information, and generate user satisfaction. Keywords: Accounting Information Systems, User Satisfaction, Financial Reporting Efficiency, Task–Technology Fit, Information System Success Model, ICSO.